2014
DOI: 10.4102/ids.v48i1.1769
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in the workplace: An introductory overview

Abstract: The research was conducted from the perspective of public practical theology, which hasthe general purpose to gain a deeper understanding of the human in all facets of his orher everyday life. More specifically, practical theology wants to facilitate the experience of meaningfulness and sense outside the walls of the church for people to be able to answer existential questions. In this article, the focus was on the individual in the workplace and the meaning of work. Corporate interest in spirituality is not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…As it becomes clear through Figure 3 that conformity quality indicators were within the required criteria for the model and it is clear through Table 3 the morale of the paragraphs, as it was found that all paragraphs are greater than the critical standard value (CR) of (1.96) and this indicates the validity of the phrases and that quality indicators The extracted match is close to the Goodness Of Fit quality indicators and is a good indicator. It should be noted here that paragraph (11,11,16,27) was deleted because it was insignificant in addition to adjusting the values of common differences by making a link between the paragraphs with the highest common variance that appeared in the recommendations of the Modification Indices [4]. As these recommendations include either deleting the paragraphs with the highest common, high variance within the model or amending them the amendment has been made and as shown in Figure 3 of the workplace spirituality variable after the amendment.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As it becomes clear through Figure 3 that conformity quality indicators were within the required criteria for the model and it is clear through Table 3 the morale of the paragraphs, as it was found that all paragraphs are greater than the critical standard value (CR) of (1.96) and this indicates the validity of the phrases and that quality indicators The extracted match is close to the Goodness Of Fit quality indicators and is a good indicator. It should be noted here that paragraph (11,11,16,27) was deleted because it was insignificant in addition to adjusting the values of common differences by making a link between the paragraphs with the highest common variance that appeared in the recommendations of the Modification Indices [4]. As these recommendations include either deleting the paragraphs with the highest common, high variance within the model or amending them the amendment has been made and as shown in Figure 3 of the workplace spirituality variable after the amendment.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…These results indicate that the use of the Internet and computers negative psychological effects did not occur to one of us and we may talk about straining our eyes and our backs and wrists as a result of the long time we spend in front of computers. It is therefore the duty of modern organizations interested in maintaining a healthy working environment for their workers and to be aware of and address these challenges, which leads to the cost of workers to stay a long time in front of computers [11]. These challenges have resulted in a clear reduction in stability and job security has increased the uncertainty and contributed to the decline of work ethics and high anxiety and the emergence of cases of fatigue and job fatigue in contemporary organizations, and without a doubt, workers who are constantly confronted with the fear of losing their jobs or suffering from the state of stress, they are likely to search for resources Which provides them or give them value and significance of the work is clear [2].…”
Section: Workplace Spirituality In the 21st Centurymentioning
confidence: 99%
“…It features a global development in which the focus has moved to the perspective that work ought to be significant and meaningful. This focus is presently on a spiritual paradigm; as a recent developing paradigm in which much advancement with regard to the understanding of the employee spiritual engagement are evolving [25]. Studies reveal that employees find it hard to disconnect their spiritual lives from their workplace environment [26].…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
“…The spiritual process would therefore be free and personal... unless it follows the path of religion. Then, both functional approaches and those advocating a redesign of work, work relations and organization based on a spiritual anthropology and paradigm put the notion of the whole person at the heart of the approach (Fairholm 1998, Mitroff and Denton 1999, Mitroff 2003, Fourie 2014. The authors stress the need to consider the whole person at work.…”
Section: A Spirituality That Is Necessarily Non-religious?mentioning
confidence: 99%
“…important part of the work on spirituality in the workplace has focused on the impact on the performance and the functioning of the organisation of taking into account the spiritual dimension of work and what is identified as the need of employees to give meaning to their activity(Jurkiewicz and Giacalone 2004, Jurkiewicz and Giacalone 2004, Benefiel et al 2014, Fourie 2014, Van der Walt 2018). Two approaches stand out.The Issues of Spirituality in the WorkplaceThe first approach groups together research that seeks to identify and define the implications of taking spirituality into account in the functioning of the organization and management practice(Jurkiewicz and Giacalone 2004, Gotsis and Kortezi 2008, Vitell 2009, Karakas 2010, Kutcher et al 2010, Fourie 2014, Naidoo 2014,Wallace et al 2017).…”
mentioning
confidence: 99%